Qualidade fisiológica de sementes de feijão carioca submetidas a dessecação em pré colheita por diferentes produtos e épocas - Bruschi, Angelo (2019)
The use of high quality physical, genetic, physiological and sanitary seeds is an important factor to obtain high yields in the bean crop. For the production of high quality seeds, it is necessary to adopt good management practices. The pre-harvest desiccation of the crop is usually used, due to the majority of the cultivars available on the market have a habit of indeterminate growth and uneven maturity. Thus, it is important to choose the correct desiccant and correct application time. The goal of this project was to evaluate and compare the physiological and physical seeds quality, produced by the combination of the use of diferent products and periods of plant’s maturation, the same was done about the productivity. The experiment was conducted in a randomized block design, in a 4x4 factorial system with four repetitions. Using four comercial products and at four diferents plant maturation periods. The best periods to obtain bean seeds with high physiological quality was at 50, 60 and 70% mature pods. The products “glifosato potássico”, “saflufenacil” and ammonium glyphosate did not reduce the physiological quality of bean seeds compared with the evidence, while “diquat” did, reducing the seed vigor. The highest productivity was reached using potassium glyphosate applied with 60% of the pods maturation.